Progression and Outcomes of Non-dysfunctional Bicuspid Aortic Valve: Longitudinal Data From a Large Korean Bicuspid Aortic Valve Registry - Song, Shinjeong; Seo, Jiwon; Cho, Iksung; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2021)
Background: Using echocardiographic surveillance, many patients are diagnosed with bicuspid aortic valve (BAV) without significant valve dysfunction. Limited data are available regarding the progression and outcomes of non-dysfunctional BAV. Methods and Results: We investigated 1,307 BAV patients (984 male, mean age 56 years) diagnosed from Jan 2003 through Dec 2018 in a single tertiary center. Seven hundred sixty-one patients underwent follow-up echocardiography at ≥1 year post-diagnosis. Non-dysfunctional BAV was defined as BAV without moderate aortic stenosis (AS) or aortic regurgitation (AR). The presence of aortopathy was defined as an ascending aorta diameter >37mm. Progression to significant BAV dysfunction, progression to severe aortopathy (ascending aorta diameter ≥45mm), and incidence of valve or aorta operation were analyzed. One hundred eighty-seven (25%) patients showed non-dysfunctional BAV. Among them, 104 (56%) had mild AS or AR, and 81 (43%) had aortopathy at indexed echocardiography. At 6.0 ± 3.8 years post-diagnosis, 56 (29%) progressed to dysfunctional BAV, 28 (15%) progressed to severe aortopathy, 22 (12%) underwent valve operation, and 19 (10%) experienced aorta operation. Eighty-nine percent of patients with normal BAV function and 61% of patients with mild AS or AR maintained non-dysfunctional BAV. More patients with aortopathy progressed to severe aortopathy (35 vs. 0% without aortopathy, p < 0.001), with a higher incidence of aorta operation (21 vs. 2%, p < 0.001). Conclusions: In patients with non-dysfunctional BAV, initial BAV function and degree of aorta dilatation might be important for progression and outcomes. Patients without any dysfunction or aortopathy tend to maintain good structure and function for 6 years.